Modeling the Structural and Cyclical Determinants of Morocco’s Trade Balance: An Econometric Approach - Bourouis, Khalil; El Yahyaoui, Mohamed; Oukhouya, Hassan; Fadlallah, Abdellali; Amine, Saida (Statistics, Optimization & Information Computing, 2026)
This study examines the dynamics of Morocco’s trade balance, with a focus on the distinction between its structural and cyclical components. Firstly, a cyclical adjustment approach is used to neutralize the effects of internal and external economic fluctuations. The rationale behind this method is based on estimating the relationship between trade volumes (exports and imports) and their fundamental factors, including domestic and foreign income and prices. Secondly, a modified version of the Hodrick-Prescott filter, known as the modified Hodrick-Prescott filter (MPHF), is employed to accurately extract the trend components from price indicators and gross domestic product (GDP). The second method of estimating income elasticities of foreign trade is through autoregressive distributed lag (ARDL) models, which allow for both short and long-run effects. In order to ensure the accuracy of these findings, sensitivity analysis is conducted on different alternative methods. Overall, there is also a more profound comprehension regarding persistent disparities in external balances, since the approach can allow for different paths for the sustainability of Morocco’s current balance. The study highlights the role of structural elements in foreign trade phenomena in Morocco, where structural differences are considered the primary cause of the country’s trade deficit. Nevertheless, import and export cycles have had minor effects.